Auto-check network reporting tool (ACNR): network monitoring / Ahmad Fakhriy Che Ariffin - Che Ariffin, Ahmad Fakhriy (2013)
A network commonly experience their error or problem. They are depending on their size of the network. Increase in the size of the network; increase the chance of experience error and problem. Indirectly, the user or technician is hard to find out the source of the problem when they got them in the large company such a large network. Main objective is to automatically identify if there are error in terms of physical and virtual problem such as routing loop problem, cabling error and device error which not function properly. Main component used in this development is python programming language. Python is one of the powerful programming languages to create a network tools. Besides that, this project use Qt software as GUI tool development. As a result expected, the tool can detect end and internetwork device in a network. It can list information about the end and internetwork device. For example, the user can know what kind of the OS used by the computer and what kind of switch and router.